MOTIVASI DAN SIKAP PERAWAT RUANGAN TERHADAP KEPATUHAN HAND HYGIENE DI RS IBNU SINA PEKANBARU - Fitra Mayenti; Otrina Otrina; Sumandar Sumandar (Jurnal Ilmiah Keperawatan, 2020)
The Risk of Infection is problem among Hospitals in Indonesia, the increase occurs continously. Nasocomial infection caused by multifactors, such as not hand hygiene before nursing intervension.The research was conducted to assess the correlation between motivation and Attitude of nurse toward obediently on hand hygiene as well as infusion of pasients in Ibnu Sina Hospital Pekanbaru. The research was used descriptf correlation with cross sectional approach. The participants were 77 participants were selected using purposive sampling Data were analyzed by univariat and bivariate and using chi-square analyzed. The result showed that there were correlation of motivation (p=0.006) and attitude (p=0,014). It is recommendation to departemen of preventive and commite control in Ibnu Sina Hospital Pekanbaru can be active give motivation among nurse.